Tied by blood, bonded in love an advocacy campaign on parental roles towards affective development of adolescence - Carreon, Bryan Russel B. (College of Fine Arts, University of the Philippines Diliman, 2017)
Proper parenting is knowing your 'parental roles'. Parents should be a responsible provider. They should provide economic security for their children by giving their children their basic needs as a child. But it goes beyond providing these basic needs of a child. But because of the new ideations influencing the parents, when sustenance is new basis of parental role, and liberalization is taking place the true meaning of 'parental role' is forgotten. Parents nowadays lack knowledge about it. They think that parenting role only includes the sustenance part forgetting the affective part. In the adolescent years of a child, developmental transition between childhood and adulthood, involving multiple physical, intellectual, personality, and social developmental change occurs. Someone must be physically present to guide them in dealing with problems that has to do with physical, psychological, emotional, and social disturbances. And best person to be with a child is only their parents. According to the research findings, out of 50 respondents 40 adolescents said that they do not share their problems with their parents. Based on the survey results from parents, they always say they're busy working to provide the needs of their children. Most of them also said that they are trying their best out to their children. Because of these reasons, Tied by blood, bonded in love : campaign on parental roles towards affective development, was made. This campaign aims to establish good communication and strong connection between parents and children by raising consciousness about parenting towards affective development of adolescents.